Time to change to improve health: clinical pharmacy and pharmaceutical care education in Turkey - Bektay, Muhammed Yunus; Sancar, Mesut; Ali Jadoo, Saad Ahmed; Izzettin, Fikret Vehbi (Journal of Ideas in Health, 2020)
The practice of clinical pharmacy had a positive impact on the profession by giving pharmacists more job opportunities. Moreover, the pharmacy began to gain the status it deserved, which was lost many years ago. In this paper, we aimed to give a brief explanation of the clinical pharmacy philosophy and definition of pharmaceutical care. What are the general and specific roles of clinical pharmacists in the modern world healthcare system? Also, how to implement clinical pharmacy in education to obtain competent pharmacists. We shared our observation and experience, specifically on the progress of implementation of clinical pharmacy education in Turkey. The stepwise method has been successfully followed in the implementation of clinical pharmacy education in Turkey. In the undergraduate program, the first step taken was the addition of clinical courses, such as the role of clinical pharmacy, patient education, etc. and practical hospital rounds (internal medicine, pediatrics, and surgery). The post-graduate program, such as master (MSc) and doctoral (Ph.D.) degrees, also offered to prepare clinically oriented pharmacy academicians. The continuous education programs were structured to implement clinical pharmacy idea for the pharmacists in practice. In conclusion, the stepwise approach significantly smoothed the transition from the product-oriented to the patient-oriented pharmacy education. Moreover, the adoption of the skills education system to educate pharmacists needs to review the policy regularly and gradually change it accordingly.